Agroecologia, sistemi agro-alimentari locali sostenibili, nuovi equilibri campagna-città - Bocchi, Stefano; Maggi, Marta (Scienze del Territorio, 2014)
Today agroecology is recognized as a new scientific paradigm useful to respond to the new sustainability challenges of both the agriculture and the agro-food system domains. Aims and contents of this discipline have changed over time and are still evolving today: conceptual tools and methodologies offered by agroecology may be usefully adopted within interdisciplinary studies related to sustainable production, consumption, exchange, settlement systems. In this paper we briefly review the history of agroecology and stress the role it plays nowadays in managing food systems and in particular short-distance food networks, intended as a new way the relationships between the countryside and the city performs.